1994
DOI: 10.1007/bf01958981
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré syndrome associated with IgM anti-GM1 antibody followingCampylobacter jejuni enteritis

Abstract: We report a 4-year-old girl diagnosed as having Guillain-Barré syndrome after infection by Penner serotype 19 of Campylobacter jejuni. The patient had the HLA-B35 antigen. Neurological examination revealed distal-dominant weakness and intact sensation. Serial electrophysiological studies indicated that the predominant process was axonal degeneration involving motor nerves. An enzyme-linked immunosorbent assay revealed the presence of high titres of serum IgM antibodies to gangliosides GM1 and GM2. The IgM auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1997
1997
2000
2000

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
1
1
Order By: Relevance
“…Our patients with CAGBS were younger than those previously described, with the exception of the patients reported by De Bont et al (2 years)3 and Sugita et al (4 years) 5. Patients reported by Kuroki et al were aged 7–14 years (median 11 years),4 whereas Yuki et al reported two patients aged 13 and 9 years with Miller-Fisher syndrome associated with campylobacter 14…”
Section: Discussioncontrasting
confidence: 51%
“…Our patients with CAGBS were younger than those previously described, with the exception of the patients reported by De Bont et al (2 years)3 and Sugita et al (4 years) 5. Patients reported by Kuroki et al were aged 7–14 years (median 11 years),4 whereas Yuki et al reported two patients aged 13 and 9 years with Miller-Fisher syndrome associated with campylobacter 14…”
Section: Discussioncontrasting
confidence: 51%
“…In severe cases, axonal degeneration may accompany the demyelination. Less frequently encountered in North America and Europe but common in China (50,100), Japan (152,175,185,186), Mexico (126), and probably other regions of world are the axonal patterns, in which axons appear to be the target of the immune attack.…”
Section: Gbsmentioning
confidence: 99%